Automated Non-invasive Video-Microscopy of Oyster Spat Heart Rate during Acute Temperature Change: Impact of Acclimation Temperature - Domnik, Nicolle J.; Polymeropoulos, Elias T.; Elliott, Nicholas G.; Frappell, Peter B.; Fisher, John T. (Frontiers in Physiology, 2016)
We developed an automated, non-invasive method to detect real-time cardiac contraction in post-larval (1.1-1.7 mm length), juvenile oysters (i.e. oyster spat) via a fibre-optic trans-illumination system. The system is housed within a temperature-controlled chamber and video microscopy imaging of the heart was coupled with video edge-detection to measure cardiac contraction, inter-beat interval, and heart rate (HR). We used the method to address the hypothesis that cool acclimation (10°C vs. 22°C – Ta10 or Ta22, respectively; each n = 8) would preserve cardiac phenotype (assessed via HR variability, HRV analysis and maintained cardiac activity) during acute temperature changes. The temperature ramp (TR) protocol comprised 2°C steps (10 min/experimental temperature, Texp) from 22°C to 10°C to 22°C. HR was related to Texp in both acclimation groups. Spat became asystolic at low temperatures, particularly Ta22 spat (Ta22: 8/8 vs. Ta10: 3/8 asystolic at Texp = 10°C). The rate of HR decrease during cooling was less in Ta10 vs. Ta22 spat when asystole was included in analysis (P = 0.026). Time-domain HRV was inversely related to temperature and elevated in Ta10 vs. Ta22 spat (P < 0.001), whereas a lack of defined peaks in spectral density precluded frequency-domain analysis. Application of the method during an acute cooling challenge revealed that cool temperature acclimation preserved active cardiac contraction in oyster spat and increased time-domain HRV responses, whereas warm acclimation enhanced asystole. These physiologic changes highlight the need for studies of mechanisms, and have translational potential for oyster aquaculture practises.